Demographic and clinical profiles of type 2 diabetes mellitus patients initiating sitagliptin in the real-world setting. (3rd July 2017) - Pawaskar, Manjiri; Liu, Jinan; Rajpathak, Swapnil; Iglay, Kristy; Engel, Samuel S.; Hannachi, Hakima
Abstract: Objective: Dipeptidyl peptidase-4 (DPP-4) inhibitors have been used for the management of type 2 diabetes (T2D) for over a decade; however, there is a limited understanding of the evolution of their use in the real-world setting over this time period. This study evaluated the demographics and clinical characteristics of patients initiating sitagliptin over a 10 year period in the United States. Research design and methods: Quintiles electronic medical records database was used to identify adults with a new prescription of sitagliptin over two 5 year time periods: 2006–2010 ( n = 57, 604), and 2011–2015 ( n = 147, 326). In addition, we also evaluated how the most recent (year 2015) profile of sitagliptin initiators ( n = 29, 295) compares to the treated T2D patients ( N = 474, 877) in 2015. Main outcome measures: No outcomes were assessed. Descriptive statistics were used to summarize baseline patient characteristics. Results: The overall demographics and clinical characteristics of patients initiating sitagliptin were generally similar over the two time periods; however, baseline HbA1c (median) was higher in the later time period: 7.6% vs. 7.9% respectively. Sitagliptin was initiated in patients across a broad range of age (18–79) years, body mass index (BMI) (10–70) kg/m 2 and HbA1c (3–20) %. The most prevalent comorbidities observed in these patients were hypertension (93%), hyperlipidemia (81%), obesity (55%), chronic kidney disease (22%) and cardiovascular disease (21%). Additionally, when we assessed the treated T2D patients and patients initiating sitagliptin in 2015, several characteristics were comparable such as age (median) (64 vs. 63) years and BMI (33 vs. 33) kg/m 2, and the most prevalent comorbidities were hypertension (97 vs. 95) %, and hyperlipidemia (86 vs. 81) % respectively. Conclusion: The overall demographic and comorbidity profile of patients initiating sitagliptin did not substantially change over the last decade and is similar to the treated T2D population.